Therapeutic Options for Left Main, Left Main Equivalent, and Three-Vessel Disease - Glazier, James J.; Ramos-Parra, Bayoan; Kaki, Amir (International Journal of Angiology, 2021)
Patients with left main, left main equivalent, and three-vessel coronary artery disease (CAD) represent an overlapping spectrum of patients with advanced CAD that is associated with an adverse prognosis. Guideline-directed medical therapy is a necessary but often insufficient treatment option, as such patients frequently need mechanical revascularization by either coronary artery bypass graft (CABG) surgery or percutaneous coronary intervention (PCI). In patients with advanced CAD presenting with acute myocardial infarction, PCI, of course, is the preferred treatment option. For stable patients with advanced CAD, CABG surgery remains the standard of care. However, observations from the SYNergy between Percutaneous Coronary Intervention with TAXus and Cardiac Surgery (SYNTAX) trial suggest that PCI may be a useful alternative in patients with three-vessel disease with a low SYNTAX score as well as in patients with left main disease and a low or intermediate SYNTAX score. In the subset of patients with diabetes mellitus, the Future Revascularization Evaluation in Patients with Diabetes Mellitus: Optimal Management of Multivessel Disease trial unequivocally demonstrated the superiority of CABG surgery in improving outcomes. The findings of the recently published Everolimus-Eluting Stent System versus Coronary Artery Bypass Surgery for Effectiveness of Left Main Revascularization and Nordic–Baltic–British Left Main Revascularization study trials point to a favorable role for PCI in certain low-to-moderate risk patients with left main stem disease.
Keywords: coronary artery disease; coronary artery bypass graft surgery; percutaneous coronary intervention; drug-eluting stents